Retention of a Small Bowel Capsule Endoscopy: Case Report - Bachar, A.; Benzidane, Kamal; Khadim, A.; Essaidi, Z.; Elabbassi, T.; Bensardi, Fz. (British Journal of Healthcare and Medical Research, 2025)
Capsule endoscopy (CE) is a revolutionary diagnostic tool introduced in 2000, enabling non-invasive visualization of the entire small intestine. Initially indicated for obscure gastrointestinal bleeding and suspected Crohn's disease, its applications have expanded since then. While CE is generally safe, capsule retention (CR) is a rare but significant complication, occurring in 1–2% of cases and up to 13% in high-risk patients. CR is defined as the failure of capsule excretion within two weeks, which can lead to asymptomatic retention or complications like obstruction and perforation. Advances in pre-procedural assessments, such as the Patency Capsule® and imaging techniques, have improved the ability to predict and prevent CR. Management of CR includes medical therapy, enteroscopy, or surgery, with most cases resolving without intervention.